Adaptation and Quality of Life among Hypertensive Patients in Wetlands: A Roy Model Study - Aridamayanti, Bernadetta Germia; Septiany, Maulidya; Agianto, Agianto; Chrisnawati, Chrisnawati; Wulandari, Shenda Maulina (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Hypertension remains a major concern in low- and middle-income countries, including Indonesia’s wetland regions such as Sungai Rangas Village, where environmental and cultural factors heighten disease burden and influence quality of life. Traditional and complementary therapies are commonly practiced, highlighting the need for culturally appropriate care models. This study examined adaptive responses and quality of life among hypertensive patients using Roy’s Adaptation Model, operationalized through an assessment instrument covering four modes: physiological, self-concept, role function, and interdependence. A quantitative descriptive design involved 120 respondents aged ≥40 years selected through purposive sampling. Data were obtained using structured interviews and the WHOQOL-BREF. Most respondents were female (56.7%), older adults (40% ≥60 years), and had low levels of education. Findings showed the highest adaptive responses in interdependence (61.7%) and self-concept (59.2%), while role function had the lowest (55%). Quality of life was highest in social relationships (mean 62.4) and lowest in psychological health (56.1). Respondents with adaptive responses in all modes were more likely to report a higher quality of life (65%). Overall, adaptation patterns in wetland environments strongly shape the quality of life. Roy’s Adaptation Model provides a culturally sensitive framework, supporting recommendations such as strengthening peer support, environment-based health education, and improved mobile health access during flood seasons.